Reinforcement of Polylactic acid (PLA) bio-composite with lignin from oil palm empty fruit bunches (OPEFB) for 3D printing application. Issue 1 (November 2021) - Pairon, M S; Ali, F; Anuar, H; Ahmad, F; Suhr, J; Mirghani, M E S
Abstract: Polylactic acid (PLA) has been used as an additive material in 3D printing due to its toxic-free and environmentally friendly property. Lignin with complex and branched chemical structures had been used as a filler to improve the mechanical strength of PLA. The availability of oil palm empty fruit bunches (OPEFB) in Malaysia had made this material a good source for lignin extraction. Thus, in this research, we aim to study the mechanical strength of PLA bio-composite material with reinforcement of lignin from OPEFB. The lignin was extracted by 1, 4-dioxane with hydrochloric acid as a catalyst. The recovery of lignin from extraction solvent was done by precipitation. The lignin was successfully extracted from OPEFB with 9.04% of lignin extraction yield. The PLA/lignin bio-composite filament with 0.1% (w/w) lignin was performed by filament extruder and then used for 3D printing. The prepared sample in the form of filament and 3D printed material was characterized for mechanical strength and surface morphology. The Young's modulus, ultimate strength and elongation at break of the PLA/lignin bio-composite sample had increased 11%, 7% and 10% respectively. After the filament was used for 3D printing, the reduction of mechanical strength had been observed. The morphology by scanning electron microscopy (SEM) confirmed the presence of lignin on the fracture surface of PLA bio-composite material. Apart from that, the interlayer adhesion had been observed in the 3D printed PLA/lignin bio-composite that caused the drop in mechanical strength of the material.